2018
DOI: 10.1159/000492972
|View full text |Cite
|
Sign up to set email alerts
|

STING SNP R293Q Is Associated with a Decreased Risk of Aging-Related Diseases

Abstract: Background: Aging is a multifactorial process driven by several conditions. Among them, inflamm-aging is characterized by chronic low-grade inflammation driving aging-related diseases. The aged immune system is characterized by the senescence-associated secretory phenotype, resulting in the release of proinflammatory cytokines contributing to inflamm-aging. Another possible mechanism resulting in inflamm-aging could be the increased release of danger- associated molecular patterns (DAMPs) by increased cell dea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 37 publications
0
26
0
Order By: Relevance
“…Cells from older subjects harbored higher levels of extranuclear DNA than cells from younger subjects, which triggered innate immune responses through the DNA‐sensing cGAS‐STING pathway (Lan et al, 2019). Lutz Hamann et al investigated the influence of a STING mutant, which led to known impaired function and found that STING SNP R293Q was associated with a decreased risk of aging‐related diseases (Hamann et al, 2019). Here, we demonstrated that elevated mtDNA release from the aged hepatocytes post‐IR, which was suppressed by STING inhibition in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Cells from older subjects harbored higher levels of extranuclear DNA than cells from younger subjects, which triggered innate immune responses through the DNA‐sensing cGAS‐STING pathway (Lan et al, 2019). Lutz Hamann et al investigated the influence of a STING mutant, which led to known impaired function and found that STING SNP R293Q was associated with a decreased risk of aging‐related diseases (Hamann et al, 2019). Here, we demonstrated that elevated mtDNA release from the aged hepatocytes post‐IR, which was suppressed by STING inhibition in macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…cGAS appears as a mediator of cell stress reactions and has been assumed to be involved in aging-related diseases [131]. This interpretation has received support by recent findings on a human Sting gene polymorphism that is associated with low-risk of aging-related diseases, presumably by reducing inflammaging [136].…”
Section: Melatonin and The Proinflammatory Networkmentioning
confidence: 99%
“…The concentrations of free circulating mtDNA have been reported to increase in elderly people relative to young adults and may contribute to low-grade, chronic inflamm-aging [14]. Protection against aging-associated chronic lung diseases was recently reported in seniors carrying a defective STING allele TMEM173 R293Q, suggesting that decreased STING sensitivity might be associated with healthy aging, likely through reduced inflamm-aging, although this warrants further assessment [103]. With a large and raising global aging population, it is critical to better understand how cells and tissues evolve with age and how this can affect the respiratory system, including the specific role of self-DNA sensing through STING pathway.…”
Section: Self-dna Aging and Senescencementioning
confidence: 99%